Post-traumatic Epidermal Cyst on the Face: Case Report: (Research, Society and Development, 2020)
The epidermal cyst (CE), also known as sebaceous cyst, is a lump similar to a lump, the same skin color, whitish, or yellowish, which has a variable size and can be single or multiple, with a hard, elastic consistency. fluctuation or pus when inflamed. They affect patients of any age, are benign and most common on the face, neck and trunk, although they can affect any region of the body. Occasionally, they cause pain and are reddish in color. The objective of this work is to report a clinical case of a patient who sought the service of Buco-maxillofacial surgery and traumatology at Hospital da Restauração, Recife-PE, with a history of swelling due to a cystic characteristic after local trauma, discussing thus, the diagnosis based on imaging and histopathological exams and its surgical treatment. C.E can represent a great risk to the patient's health, since it can generate significantly deleterious effects, ranging from large aesthetic defects to airway obstruction, which can promote death, if not handled correctly. Thus, it is necessary to emphasize the need for the surgeon's knowledge, so that in this way the diagnosis and treatment are effective and the patient is minimally affected by the morbidities of this pathological entity.